Brecha digital de género y los determinantes del uso de Internet móvil en las mujeres artesanas textiles en el departamento de Puno, Perú; Digital gender gap and the determinants of mobile Internet use in women textile artisans in the department of Puno, Peru - Alfredo Pelayo Calatayud Mendoza; Bestsabe Aurora Llerena Zea; Edgar Villahermosa Quispe; Patricia Schettini; Ludwing Roald Flores Quispe (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The first objective was to estimate the digital gender gap in the department of Puno in the year 2021. For this, the probit regression model with sample selection called Heckprobit was applied using data from the Residential Survey of Telecommunications Services for the year 2021 (Erestel, 2021) of the Supervisory Agency for Private Investment in Telecommunications (Peru). The second objective was to identify the determinants of the frequency of mobile Internet use in women dedicated to textile crafts in the department of Puno, for which the censored Poisson regression model was applied with primary data collected through a questionnaire, the simple random sample technique was used. The results show the existence of the digital gender gap, men are more likely to access mobile Internet by 5.4 percentage points compared to women. On the other hand, the results corroborate that the frequency of mobile Internet use was even lower for older artisan women (p<0.01), with fewer years of education (p<0.10), if they reside in a rural area (p<0.01) and if they have limited mobile Internet service (p<0.05), the digital gender gap persists and it is imperative that the Ministry of Women and Vulnerable Populations and the municipalities undertake actions to promoting the closing of the gender gap, within the framework of the sustainable development goals of the millennium in the world agenda 2030 of the United Nations (UN).
Keywords: C34; C35; 330; Access; use; mobile Internet; women; digital divide; censored